Inverted U-shaped relationship between coffee consumption and serum uric acid in American chronic kidney disease population - Song, Jianling; Li, Hong; Fang, Xiangdong (Frontiers in Nutrition, 2023)
The objective of this study was to examine the contentious relationship between coffee consumption and serum uric acid (SUA) levels, specifically within American population with chronic kidney disease (CKD).: A total of 23,381 participants from the 2001-2018 National Health and NutritionExamination Survey (NHANES) were selected for inclusion in this investigation. Linear regression models and generalized additive models with smooth curve fitting were employed to analyze the association between log coffee consumption and serum uric acid levels. Furthermore, the robustness of the findings was assessed across diverse populations.The results of the linear regression analysis indicate a positive and marginally statistically significant (p=0.0307) association between log coffee consumption and SUA, even after controlling for other variables. Furthermore, the generalized additive model revealed a nonlinear relationship characterized by an inverted U-shape between log coffee consumption and SUA. The inflection point, identified as 11.43 g/day, marks the point at which this relationship changes direction. Moreover, this inverted U-shaped relationship was consistently observed across various subgroups, including gender, age (<60 and ≥60 years), hypertensive and non-hypertensive individuals, those with and without cardiovascular disease, non-diabetic individuals, and those who consumed coffee with or without caffeine or sugar.Conclusions: An inverse U-shaped correlation has been observed between log coffee consumption and SUA levels. This finding implies that once coffee consumption surpasses a specific threshold, it promotes a decline in SUA levels.